(3bdGOI GdfMQ aj hajGJ CYjGf GdOgQs - (3YHO Gddg Hf YHO Gddg Hf CMeO eNQeI, CHh eMeO , GdWjH HGeNQeI,J (B947 (3g` s ((3jMji Hf CMeO Hf Ydi GdUYOi GdTGaYi s)
(3BNQgG (B:s
(3GfJgi eG hLOfGg ef gPG GdJGQjN HNW GdeUfa s
(3GdehLhO efg GdLRA GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B45s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B240 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B237 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B- (3eUhQI ef fSNI jfi LGeY GdCSJGfI (B((3JGQjN (B167) s
Keywords: (3GdJGQjNs